Pemanfaatan Markah Molekuler dalam Proses Seleksi Pemuliaan Tanaman - Muhammad Azrai (Jurnal AgroBiogen, 2005)
DNA-based technology has dramatically enhanced the efficiency of plant breeding, especially when selections are to be done under unfavourable conditions. Although significant strides have been made in crop improvement trough phenotypic selections for ergonomically important traits, this often encounters considerable difficulties, particularly those posed by genotype x environment interactions. Besides testing procedure may be many times difficult, unreliable or expensive due to the nature of the target traits (e.g. abiotic and biotic stresses) or the target environment. The most widespread use of Marker Assisted Selection (MAS) to date is to assist backcrossing of major gene already proven elite cultivars. If individual genes or Quantitative Trait Loci (QTL) significantly influencing specific target traits can be identified based on their linkage to molecular markers, the efficiency of incorporating the desired traits in elite germplasm could be greatly enhanced. By combining QTL approach with backcrossing, useful genes that control quantitative traits have been identified in plant germplasm that are not for agriculture and have successfully been transferred to danced breeding lines. Indonesian molecular breeders should have a research program on DNA marker work that leads to application of useful selection tools and valuable germplasm. As molecular breeders adopt more rigorous experimental guidelines and ambitious goals, they also need to integrate the growing body of knowledge from genomics and bioinformatics.